Abandono y prevalencia del tabaquismo: sexo, clase social y atención primaria de salud() - Villalbí, Joan R. (Aten Primaria, 2008)
OBJECTIVE: To analyse the joint role of social class and primary health care in giving up smoking. DESIGN: Cross-sectional study. SETTING: Barcelona (Catalonia, Spain), 2000-2001. PARTICIPANTS: A sample of the resident non-institutionalized population, restricted to people aged 15-50 who have a habitual primary care source (n=4178). MAIN MEASUREMENTS: These were obtained from the Barcelona Health Interview Survey. Independent variables include sex, social class and usual source of primary health care. Dependent variables are having ever been a smoker, having quit, and being a current smoker. Age-adjusted proportions were calculated (95% CI). RESULTS: Social class shows that more manual workers have been smokers. Men smoked more than women. Overall quitting is similar in both sexes.Quitting showed a social gradient in men. Measurement of source of care showed quitting was higher among users of private clinics, but CI overlapped. On stratifying the source of Primary Care by social class, an effect seemed to emerge for men, but the CI overlapped. Prevalence at the time of the survey was higher for men; a class gradient in current prevalence emerged for men, but was less visible for women, where CI overlapped. CONCLUSIONS: Social class is a powerful determinant of smoking. Men in low-classed jobs are at greater risk of starting to smoke, are less likely to give up, and smoke more. The proportion of quitting seems lower in of public clinics service users. Health advice is efficacious, but in population terms other factors seem to have greater influence.